Ethical challenges in the leader-follower relationship. - Hollander, Edwin P. (Business Ethics Quarterly, 1995)
Part of a special section on business ethics and leadership in the 1990s. The ethical challenges in the use of authority and power are examined. Leadership and followership are unified in an interdependent relationship that is demonstrated by the notion of teamwork. Ethical concerns are among the valuational components that are vital to developing loyalty and trust in this relationship. However, due to their need to maintain power and distance, self-serving leaders may become detached from how their behavior is perceived and responded to by followers. This trend can be particularly detrimental to teamwork when leaders continue to receive disproportionate rewards despite their bad performance, particularly when combined with organizational downsizing and layoffs. Implications are drawn concerning the ethics of equity, responsibility, and accountability in the use of authority and power.